The transcervical expulsion of a large fibroid. (24th September 2012) - Stott, Daniel; Zakaria, Muhannad
Abstract : A 46-year-old woman presented to the emergency gynaecology unit at the Royal Free Hospital, London, with lower abdominal pain and offensive per vagina discharge. These symptoms developed following a recent uterine artery embolisation around 3 weeks earlier at the same hospital. After initial treatment with antibiotics, this patient re-presented with a fibroid which had prolapsed through the cervix, resulting in pain, distress and more profuse vaginal discharge. This necrotic fibroid was morcellated and removed in theatre. She made an uneventful recovery and was able to go home the following day.